FAKTOR- FAKTOR YANG MENYEBABKAN STATUS GIZI KURANG PADA BALITA DI WILAYAH KERJA PUSKESMAS SAIL PEKANBARU TAHUN 2016 - Berliana Irianti (Midwifery Journal: Jurnal Kebidanan UM. Mataram, 2018)
Abstract:  Nutrition status is a health condition of a person's body or a group of people caused by consumption, absorption and the use of nutrients. Factors leading to undernourishment in under-five children: Overcrowded birth, socioeconomic, ignorance of food and health relationships, prejudice against certain food items, overabundance of certain types of food, infectious diseases. The purpose of this study to determine the factors that cause underweight nutritional status in infants in the working area of sail health center in 2016. Quantitative research type and descriptive research design. The location of the research was conducted in the working area of Sail Health Centre and the time of the research on February 15-20, 2016. The population of mothers who had under-five children with less nutritional status in Sail Health Centre were 20 cases and all were used as research samples. The research instrument uses check list and data collection techniques using primary data. The result showed that from 20 respondents, the majority of knowledge factors of mothers who have under five children with low nutritional status are low knowledge as many as 11 people (55%), and the majority of factors of economic level of parents are low as many as 12 people (60%) and majority of birth distance factor which is too tight as many as 12 people (60%). From the results of this study, the researcher hopes to become input material of health institution by improving mother's knowledge about nutrient status less on toddler through counseling from health officer and providing supplementary food for the toddler